S126 Molecular epidemiological analysis suggests cross infection with pseudomonas aeruginosa is rare in non-cystic fibrosis bronchiectasis. (14th November 2013) - De Soyza, A; Perry, A; Hall, AJ; Sunny, S; Walton, KE; Mustafa, N; Turton, J; Kenna, DT; Winstanley, C
Abstract : Background: Non Cystic Fibrosis Bronchiectasis (NCFBr) is a cause of significant morbidity and mortality. Pseudomonas aeruginosa, a key pathogen in NCFBr, is associated with premature mortality. Globally, common clones of P. aeruginosa have been recognised from clinical and environmental sources and in Cystic Fibrosis (CF) cross infection is known to occur. There are no robust data on cross infection in NCFBr. This evidence gap impacts on managing patients but was omitted from the BTS 2010 guidelines due to the paucity of data. Aims: To seek evidence of cross infection amongst NCFBr patients. Methods: Single centre cross sectional study: We studied 50 P. aeruginosa isolates from 40 NCFBr patients using two genotyping techniques (both blinded); an Array Tube (AT) method and Variable Number Tandem Repeat (VNTR) analysis. We included known CF clonal strains as internal controls. We then compared the data using genotype databases. Results This is the largest cross infection study to our knowledge. We demonstrated that shared P. aeruginosa NCFBr genotypes were infrequent. Twelve patient isolates did not match any other isolate within the NCFBr collection or the databases. The most common clone, clone C (10%), is also known to be abundant in the environment. In ten patients where longitudinal isolates were examined, paired isolates gave matching genotyping data suggesting persistent infection. There was incomplete concordance between the Array-Tube and VNTR methods (88% agreement). Conclusion: There were no dominant Pseudomonas aeruginosa clones in NCFBr suggesting that the most prevalent mode of infection is sporadic and cross infection is rare. This may reflect the local infection control measures however. Multicentre studies are suggested to further assess the risks.